Лжебогиня: фантастический роман / В. М. Чернованова - Чернованова Валерия Михайловна (Альфа-Книга, 2015)
Экземпляры: Гобгуртская библиотека (20150612) / Инвентарный номер: 201823 / Цена: 228.36 / Авт.знак: Ч-49 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6